Comparing socio-economic inequalities in healthy ageing in the United States of America, England, China and Japan: evidence from four longitudinal studies of ageing. Issue 7 (9th July 2021) - Lu, Wentian; Pikhart, Hynek; Sacker, Amanda
Abstract: Healthy ageing has become a popular topic worldwide. So far, a consensus measure of healthy ageing has not been reached; and no studies have compared the magnitude of socio-economic inequality in healthy ageing outside Europe. This study aims to create a universal measure of healthy ageing and compare socio-economic inequalities in healthy ageing in the United States of America (USA), England, China and Japan. We included 10, 305 American, 6, 590 English, 5, 930 Chinese and 1, 935 Japanese participants for longitudinal analysis. A harmonised healthy ageing index (HAI) was developed to measure healthy ageing multi-dimensionally. Educational, income and wealth rank scores were derived accounting for the entire socio-economic distribution and the sample size of each category of socio-economic indicator. Associations between socio-economic rank scores and HAIs were assessed using multi-level modelling to calculate the Slope Indices of Inequality. Healthy ageing trajectories were predicted based on the full-adjusted age-cohort models. We found that education was a universally influential socio-economic predictor of healthy ageing. Moving from the highest to the lowest educational groups was associated with a 6.7 (5.2–8.2), 8.2 (6.0–10.4), 13.9 (11.4–16.3) and 6.1 per cent (3.9–8.2%) decrease in average HAI at 60 years in the USA, England, China and Japan, respectively. After 60 years, the educational inequality in healthy ageing kept increasing in the USA and China. The educational inequality in healthy ageing in China was also greater than any other socio-economic inequality in the four countries. Wealth was more influential in predicting healthy ageing inequality among American, English and Japanese participants, while income was more influential among Chinese participants. The socio-economic inequality in healthy ageing in Japan was relatively small. Chinese and American participants had worse healthy ageing profiles than Japanese and English participants.